The relationship between monetary base and monetary aaggregates in asean - 5 - Ng,, Chai Chet. (Universiti Malaysia Sarawak, UNIMAS, 2007)
he purpose of this study is attempted to inve stigate the existence of causal relationship between monetary base and monetary aggregates (M1 and M2) for ASEAN - 5 using the time series data from 1990:Q1 to 2005:Q4. This study is conducted by employing three methods, which are Augmented Dickey - Fuller (19 79) unit root test, Johansen - Juselius (1990) cointegration test and Granger causality test. Only Singapore and Thailand show a significant long - run cointegrating vector between monetary base and monetary variables, which are M1 and M2 respectively. The res t of the ASEAN - 5 countries fail to show a long - run relationship between the variables. The causality test results show that in general there is not uni - directional with causality running from monetary base to monetary aggregates in ASEAN - 5. Thus, monetary targeting is inappropriate used as a monetary policy in ASEAN - 5. In particular, policy should be designed to improve and strengthen the monetary and financial market in order to get better controlling in money supply process. Each ASEAN - 5 country has to en sure the selected intermediate target must be measurable, controllable and predictable.